HUBUNGAN PENGETAHUAN, PERSEPSI DAN PERILAKU PETANI DALAM PENGGUNAAN PESTISIDA PADA LINGKUNGAN DI KELURAHAN MAHARATU KOTA PEKANBARU (Jurnal Kajian Lingkungan, 2014)
This research aims to study farmerâs knowledge, perception and behavior on pesticide handling according to his social economic level, to study the perception and behavior of pesticide handling according to the farmerâs knowledge, to study the behavior of pesticide handling according to the farmerâs perception, and to formulate alternative guideline for pesticide handling to reduce the risk to environment.This collected data was interview and observation. It used cross sectional technique in data collection, using 50 samples from a total population of 266 people. The data were processed and analysed in a cross tabulation, followed with a statistic correlation test Range Spearmanâs. The result of research shows that the farmerâs levels of social economy in Maharatu Village, Pekanbaru City is low, levels of knowledge, perception, and behavior towards pesticide handling by farmers are relatively high. The social economic level shows a significant correlation but gives small effect to the behavior in pesticide handling. The farmerâs levels of social economic shows a significant correlation and gives big effect to the knowledge and perception in pesticide handling. The farmerâs knowledge shows a significant correlation and gives big effect to the perception and behavior in pesticide handling. The farmerâs perception about pesticide shows a significant correlation and gives big effect to the behavior in pesticide handling to the environment.Keywords: Perception, Behaviour, Pesticide, Environment.